Prognostic value of intraductal carcinoma for adjuvant radiotherapy candidates after radical prostatectomy. Issue 6 (8th March 2021) - Karakoc, Sedat; Celik, Serdar; Kaya, Nilhan; Bozkurt, Ozan; Ellidokuz, Hulya; Tuna, Burcin; Yorukoglu, Kutsal; Mungan, Mehmet Ugur
Abstract: Objective: To investigate the prognostic significance of intraductal carcinoma of the prostate (IDC‐P) in radical prostatectomy (RP) specimens and predictive value of IDC‐P for biochemical recurrence and adjuvant therapy decision. Method: We retrospectively evaluated patients who were performed RP between 2000 and 2014. Among, 67 patients who had stage pT3a tumour with negative surgical margin (Group 1, n = 35) and who had stage pT2 tumour with positive surgical margin (Group 2, n = 32) were included in the study. RP specimens were re‐evaluated for the presence of IDC‐P component and other prognostic factors. In both the groups, prognostic factors were compared according to the presence of IDC‐P and biochemical recurrence status. Results: In Group 1, IDC‐P was detected in five cases and biochemical recurrence was detected in three cases. Patients with IDC‐P showed significantly higher biochemical recurrence than those without IDC‐P ( P = .002). In univariate analysis, IDC‐P was found to be significantly associated with worse progression‐free survival ( P < .001). In Group 2, IDC‐P was detected in four cases and biochemical recurrence was detected in 10 cases. Also, tumour volume was significantly higher in patients with IDC‐P than those without IDC‐P ( P = .02). IDC‐P was also significantly associated with worse progression‐free survival in Group 2 ( P = .033). Conclusions: In both the groups, IDC‐P was a prognostic factor for progression‐free survival and/or biochemical recurrence. Especially in these patients, the presence of IDC‐P might be helpful for postoperative adjuvant therapy management decision.